Bacteroides fragilis enterotoxin induces cytoskeletal changes and surface blebbing in HT-29 cells. - Donelli, G (1996)
Certain strains of the anaerobic bacterium Bacteroides fragilis are known to produce an enterotoxin of about 20 kDa which is able to induce a fluid response in ligated intestinal loops and a cytotoxic response in HT-29 cells. It presents protease activity, belonging to a family of metalloproteases termed metzincins. In order to investigate the mode of action of the enterotoxin in cultured cells, we performed a study with HT-29 cells, using both fluoresence and electron microscopy. Treated cells underwent morphological changes, mainly consisting of the retraction of the cell body and the formation of numerous blebs on the cell surface. The microfilament system was reorganized, the F-actin being condensed as a ring at the cell periphery, whereas other cell organelles appeared to be unaffected. All these changes, clearly visible after 3 h of exposure to the toxin, were reversed within 24 h of treatment. By inhibiting the protease activity of the toxin with specific metal chelators, the cytoskeletal effects were also prevented. Thus, B. fragilis enterotoxin appears to act on cells by reversibly modifying the actin cytoskeleton, an effect probably dependent on its proteolytic activity.